Race and the death penalty in Kentucky murder trials: 1976–1991 - Keil, Thomas J. (American journal of criminal justice, 1995)
This study re-examines the effect of race of the victim on the probability that an accused murderer is charged with a capital crime and sentenced to death in Kentucky. It adds over five years of data to our original study. The results show that Blacks accused of killing Whites had a higher than average probability of being charged with a capital crime (by the prosecutor) and sentenced to die (by the jury) than other homicide offenders. This finding remains after taking into account the effects of differences in the heinousness of the murder, prior criminal record, the personal relationship between the victim and the offender, and the probability that the accused will not stand trial for a capital offense. Kentucky’s “guided discretion” system of capital sentencing has failed to eliminate race as a factor in this process.